A Case Report On Mild Symptomology -Antiphospholipid Antibody (Apla) - A.D, Dharshini; Praveen. S, Rakkesh; Dheenadhayalan, M.; Karthickeyan, K.; Shanmugasundaram, P.; Sundar Sri, M. K. (Journal of Neonatal Surgery, 2025)
Antiphospholipid Antibody (APLA) Syndrome is an autoimmune condition marked by a hypercoagulable state, which predisposes individuals to thrombosis in both arterial and venous vessels throughout the body. This disorder is commonly associated with complications such as thromboembolic events and pregnancy issues. According to population-based studies, the estimated incidence ranges from 1 to 2 cases per 100,000 individuals, while the prevalence is reported to be between 40 and 50 cases per 100,000. APS can present as a primary or as a secondary condition in association with Systemic Lupus Erythematosus (SLE) or other autoimmune diseases. APLA is a diverse and can vary from clinical presentation. Therefore here, a case of 21year old female patient presented with complaints of numbness in left UL for 6 months, neck pain in (R) side. At the age of 5, the patients had medical history of jaundice and the patient had persistent headache and was worsen and Brain MRI showed (L) Thalamic infarct hypoplasia transverse and sigmoid colon. The patient was treated with initial stage of first line medication such as blood transfusion, multivitamin and analgesic medication. Here, I have presented with antiphospholipid antibody syndrome patient with observed minor complication such as splenomegaly, constipation, calcified granuloma which was detected in CT whole abdomen. In MRI with lumbar spine screening showed mild disc bulging with small profusion in the lumbar region.